The role of information professionals in academic libraries in Malaysia / Asmad Rizal Umar and Atirah Ruslan - Umar, Asmad Rizal; Ruslan, Atirah (Faculty of Information Management, 2014)
This article discusses the role of information professionals in academic libraries in Malaysia. It begins with the clarification on the concept of information professional and then it highlights the main role of the information professional in enhancing the academic library services in Malaysia. This article also highlights the responsibilities of information professionals in electronic era. Information professionals nowadays need to adapt the changes and the significance of information technology in order to support the process of teaching, learning and research. It also highlights the role of an academic librarian in providing effective reference and information services efficiently and this would contribute to the learning, teaching and research in higher learning institutions.